Simbiosis Verde (2021)
Colonial city Santa Fé de Bogotá developed from its rivers and streams that descended from the eastern hills. Historically, there has always been an intimate connection between humanity and their natural environment. These water streams not only fulfilled a role for personal hygiene, but the supply in public spaces was crucial to generate congregation spaces. However, urban designers did not perpetuate with these dynamics within our city. The final thesis Green Symbiosis suggests a critical perspective to the current ongoing urban project proposed by the district and aims to open the discussion around the environmental dynamics and preservation of native species in public spaces within the capital